A new species of the genus Asthenara Förster, 1869 (Hymenoptera, Ichneumonidae) from Mexico with identification key - Reshchikov, Alexey (Zootaxa, 2016)
The genus Asthenara Förster, 1869, belonging to the tribe Pionini of the subfamily Ctenopelmatinae (Hymenoptera, Ichneumonidae), comprises eight described species (Yu et al. 2012). Two of them are distributed in the Palaearctic Region, and six in the Neotropical region. One Neotropical species is known from Costa Rica (Gauld et al. 1997), the remaining five from Mexico (Kasparyan 2006). Kasparyan (2006) provided a key to the species from the Mexico. To date, no species of the genus have been described from Nearctic region or south of Costa Rica. In this article a new species belonging to Asthenara, collected in the Mexican state of Jalisco is described.